Undergraduates May Prefer to Learn about the Library Informally - Miller, Robin Elizabeth (Evidence Based Library and Information Practice, 2015)
A Review of: Murphy, J. A. (2014). Library learning: Undergraduate students’ informal, self-directed, and information sharing strategies. Partnership: The Canadian Journal of Library and Information Practice and Research, 9(1), 1-20. https://journal.lib.uoguelph.ca/index.php/perj/index Abstract Objective – To determine undergraduate student approaches to learning about research and to seeking assistance with resources and services offered by the library. Design – Three face-to-face focus groups received the same 12 questions to discuss over 90 minutes. Setting – Academic library in Saskatchewan, Canada. Subjects – A total of 14 undergraduate students majoring in a social science or humanities subject area. Of these, four subjects were in their second year of undergraduate study, four in their third year, and six in their fourth year. Subjects participated in focus groups with other students in their year of study. The researcher recruited subjects through printed advertisements distributed in areas frequented by social science and humanities students. 12 female students and 2 male students participated. 13 participants had attended a library instruction session in the past. Subjects were offered pizza, but were not otherwise incentivized to participate. Methods – The researcher and an assistant conducted three focus groups with undergraduate students, eliciting qualitative comments later transcribed and coded manually for analysis. Requirements for participation included being engaged in an undergraduate major in the social sciences or humanities, and previous experience using the library. Subjects answered open-ended questions about their studies, research activities, use of the library for a variety of tasks, and help seeking preferences. Main Results – Regardless of year of study, focus group participants reported informal approaches to learning about and conducting research. All participants were confident about using the library’s online resources, and preferred learning about library resources through self-directed practice and trial and error. Participants revealed that learning about the library informally was preferable to library instruction. Most participants indicated they had sought help from the library at one time or another. Participants prized sharing information with classmates, especially through collaboration and social networks, and they valued the expertise of professors, peers, friends, and family when doing research. Three factors may influence their choice to consult and exchange information with other trusted advisers outside of the library: convenience, familiarity, and knowledge. Conclusion – Findings from this study align with previous findings about student approaches to seeking research assistance. The author reveals that assistance from the library, including library instruction, is less important to focus group participants than the research strategies they have developed informally, including trial and error and information sharing within one’s personal network. The author observes that the informal learning strategies implemented by undergraduates in this study mirror the strategies of adult learners, especially in the workplace. The author suggests that intentional, course integrated library instruction in the early years of undergraduate education would strengthen students’ preferred self-directed learning about research.